Business Retention and Expansion (BRE) Programs: Making Your (Power) Point - Henry M. Cothran (EDIS)
FE713, a 4-page fact sheet by Henry M. Cothran, is part of the Business Retention and Expansion Programs series. It provides an overview and a set of guidelines for developing effective visual presentations that won’t leave your audience snoring or lost. Includes references. Published by the UF Department of Food and Resource Economics, June 2008.